A negative binomial thinning‐based bivariate INAR(1) process. (28th May 2020) - Zhang, Qingchun; Wang, Dehui; Fan, Xiaodong
Abstract : This article considers a bivariate INAR(1) process based on an extension of the negative binomial thinning operator by prespecifying the distribution of the innovations. The dependence is introduced through the innovation components. The existence, uniqueness, strict stationarity, ergodicity, and some probabilistic properties of the process are derived. The estimation methods of conditional least squares and conditional maximum likelihood are considered. Some numerical results of the estimates are presented by simulation study. An application to crime data set is provided.